Molecular Characteristics and Antibiotic Resistance Profiles of Klebsiella Isolates in Mthatha, Eastern Cape Province, South Africa - Sandeep Vasaikar; Larry Obi; Isaac Morobe; Mary Bisi-Johnson (International Journal of Microbiology)
The increase in the incidence of extended-spectrum β-lactamase- (ESBL-) producing Klebsiella species has become a serious problem worldwide, because of their incrimination in antibiotic resistance. The objective of this study is to investigate the resistance genes responsible for ESBL-producing Klebsiella species and carbapenemase-producing Klebsiella (CRE) isolated in Mthatha and to study their epidemiology. A prospective, descriptive study of 202 nonrepetitive samples from patients was obtained from Nelson Mandela Academic Hospital. The cultured Klebsiella isolates were subjected to antimicrobial susceptibility tests and the polymerase chain reaction of blaCTX-M, blaTEM, blaSHV, blaKPC, and blaNDM genes. Overall K. pneumoniae were the majority with 169 (83.7%) species isolates, followed by K. oxytoca with 29 (14.4%), while K. ozaenae and Raoultella ornithinolytica were 2 (0.9%) each. The prevalence of ESBL production in all Klebsiella species was 117 (57.9%). ESBL-genotypic resistance is driven in Mthatha by blaSHV 121 (77.1%) followed by blaTEM 105 (66.9%) and blaCTX-M at 89 (56.7%). The most common ESBL genotype combination among the Klebsiella was blaTEM+blaSHV + blaCTX-M at 79 (50.3%). There is a steady increase in the rate of ESBL genes in the last five years.